The Development of Industry Based Innovative Teaching Factory Leadership at SMKN 2 Payakumbuh - Budi Dharmawan; Ambiyar Ambiyar; Hasan Maksum (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to develop an innovative leadership model in the implementation of industry-based teaching factory at SMKN 2 Payakumbuh. Teaching factory is a learning approach that integrates education with industry to enhance students' competencies in accordance with labor market demands. However, its successful implementation is highly influenced by leadership quality within the school. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation. The research subjects included the principal, vocational teachers, and industry partners. Data analysis was conducted using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that effective innovative leadership in industry-based teaching factory is characterized by visionary thinking, collaboration, adaptability to change, and strong industry partnership orientation. The developed leadership model emphasizes continuous integration between school management and industrial needs. The implications of this study are expected to contribute to policy and leadership practices development in vocational high schools.